MENINGKATKAN KEMAMPUAN MEMBACA INTENSIF SISWA KELAS VII SMP MUHAMMADIYAH 2 KOTA TERNATE DENGAN MENGUNAKAN METODE STRUKTUR ANALITIK SINTETIK (SAS) - Darlisa Muhammad; Rajina R. Senen (Cakrawala Bahasa, 2022)
The aims of this research are (1) to find out how to improve the intensive reading ability of Class VII students of SMP Muhammadiyah 2 Ternate City before using the SAS Method. (2) to find out how to improve the intensive reading ability of Class VII students of SMP Muhammadiyah 2 Ternate City after using the SAS method. The method used in this research is quantitative description method. The population and sample in this study were all students of Class VII SMP Muhammadiyah 2 Ternate City, totaling 25 students. Data collection techniques used in this study are (1) Tests (Pretest and Posttest), (2) Observation, (3) Interview. Data analysis is quantitative description. From the data analysis and conclusions, it can be seen that (1) the initial test of students who got a score of 85-100 very good qualifications amounted to 1 student by 5%, students who got a score of 75-85 good qualifications amounted to 7 students by 35%, students who got score ranges from 65 to 74 sufficient qualifications amounted to 2 students by 10%, and students who obtained a score range from 55 to 64 with less qualifications amounted to 15 students by 75%, (2) Final test. Students who obtained a score range of 86-100 very good qualifications amounted to 4 students by 20%, students who obtained a score range of 75-85 with good qualifications (B) amounted to 15 students by 75%, and there were no students who obtained a score range of 55-64 less qualification (K). So it can be concluded that there was a very significant change between the initial test and the final test using the Synthetic Analytical Structure Method (SAS) class VII students of SMP Muhammadiyah 2 Ternate City had been able or succeeded in increasing intensive reading skills..